ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI (Studi Empiris pada Pegawai Direktorat Jenderal Perbendaharaan Kementerian Keuangan di Kota Semarang) - Komang Yuli Pridarsanti; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the determinants of employees’ performance in Direktorat Jenderal Perbendaharaan (DJPBN) Kementerian Keuangan in Semarang City. Data collection was conducted by questionnaire survey method on the non-managerial employees of Kantor Wilayah DJPBN Provinsi Jawa Tengah and Kantor Pelayanan Perbendaharaan Negara Semarang II. Using primary data collected from 107 respondents, employees’ performance was regressed on work motivation, work competency, role perception and perceived organization support. Multiple regression model was employed to analyze the data. The results of this study indicate that : (1) work motivation has positive and significant effect on employees’ performance, (2) work competency has positive and significant effect on employees’ performance, (3) role perception has no significant effect on employees’ performance,and (4) perceived organization support has no significant effect on employees’ performance